Reduction in undiagnosed HIV infection in the European Union/European Economic Area, 2012 to 2016 - van Sighem, Ard (2018)
Members of the Ecdc HIv/Aids Surveillance And Dublin Declaration Monitoring Network: Portugal: Isabel Aldir, Helena Cortes Martins, Teresa Melo.